A multicenter trial of current trends in the diagnosis and management of high-grade pancreatic injuries. Issue 5 (May 2021) - Biffl, Walter L.; Zhao, Frank Z.; Morse, Bryan; McNutt, Michelle; Lees, Jason; Byerly, Saskya; Weaver, Jessica; Callcut, Rachael; Ball, Chad G.; Nahmias, Jeffry; West, Michaela; Jurkovich, Gregory J.; et al.
Abstract : BACKGROUND: Outcomes following pancreatic trauma have not improved significantly over the past two decades. A 2013 Western Trauma Association algorithm highlighted emerging data that might improve the diagnosis and management of high-grade pancreatic injuries (HGPIs; grades III–V). We hypothesized that the use of magnetic resonance cholangiopancreatography, pancreatic duct stenting, operative drainage versus resection, and nonoperative management of HGPIs increased over time. METHODS: Multicenter retrospective review of diagnosis, management, and outcomes of adult pancreatic injuries from 2010 to 2018 was performed. Data were analyzed by grade and time period (PRE, 2010–2013; POST, 2014–2018) using various statistical tests where appropriate. RESULTS: Thirty-two centers reported data on 515 HGPI patients. A total of 270 (53%) had penetrating trauma, and 58% went directly to the operating room without imaging. Eighty-nine (17%) died within 24 hours. Management and outcomes of 426 24-hour survivors were evaluated. Agreement between computed tomography and operating room grading was 38%. Magnetic resonance cholangiopancreatography use doubled in grade IV/V injuries over time but was still low. Overall HGPI treatment and outcomes did not change over time. Resection was performed in 78% of grade III injuries and remained stable over time, while resection of grade IV/V injuries trended downward (56% to 39%, p = 0.11). Pancreas-related complications (PRCs) occurred more frequently in grade IV/V injuries managed with drainage versus resection (61% vs. 32%, p = 0.0051), but there was no difference in PRCs for grade III injuries between resection and drainage. Pancreatectomy closure had no impact on PRCs. Pancreatic duct stenting increased over time in grade IV/V injuries, with 76% used to treat PRCs. CONCLUSION: Intraoperative and computed tomography grading are different in the majority of HGPI cases. Resection is still used for most patients with grade III injuries; however, drainage may be a noninferior alternative. Drainage trended upward for grade IV/V injuries, but the higher rate of PRCs calls for caution in this practice. LEVEL OF EVIDENCE: Retrospective diagnostic/therapeutic study, level III Abstract : Supplemental digital content is available in the text.